(untitled) (Medico Legal Update, 2020)
It is important for hospitals to have the right marketing strategy, with marketing programs conducted can improve the quality of service, with good service quality, it will be able to satisfy customers so that customers will be loyal. This study aims to determine the relationship between the mixed marketing with patient loyalty in the Syekh Yusuf Gowa Regional Hospital. This type of research is an observational study with a cross sectional study approach. The population in this study were all inpatients who used services at the SyekhGowa Regional General Hospital in a amonth. The sampling method was done by accidental sampling, which is 114 respondents. Data analysis in this research was carried out by testing hypotheses through the correlation test method. Bivariate analysis with correlation test shows that there is a relationship between the mixed promotion (P = 0,000), mixed service provider (P = 0,000), mixed physical facility (P = 0.012) and patient loyalty, but there is no relationship between the mixed process (P = 0.064) with patient loyalty. So, there is a relationship between the mixed marketing of promotion, mixed marketing of service presenters, mixed marketing of physical facilities and patient loyalty.